Charter School Operations and Performance Evidence from California - Zimmer, Ron (RAND Corporation, 2003)
The report analyzes an array of issues pertaining to accessibility, student achievement, governance, and operation of charter schools in California. Four specific research questions were investigated: (1) What population of students attends charter schools? (2) Is student achievement higher in charter schools than in conventional public schools? (3) What oversight and support do the chartering authorities provide? (4) How do charter schools differ from their conventional public school counterparts in terms of their operation, including finances, academic achievement, and staffing?